2005
DOI: 10.1021/ic050181b
|View full text |Cite
|
Sign up to set email alerts
|

Assembly of Azido- or Cyano-Bridged Binuclear Complexes Containing the Bulky [Mn(phen)2]2+Building Block:  Syntheses, Crystal Structures, and Magnetic Properties

Abstract: Two new cyano-bridged heterobinuclear complexes, [Mn(II)(phen)2Cl][Fe(III)(bpb)(CN)2] x 0.5CH3CH2OH x 1.5H2O (1) and [Mn(II)(phen)2Cl][Cr(III)(bpb)(CN)2] x 2H2O (2) [phen = 1,10-phenanthroline; bpb(2-) = 1,2-bis(pyridine-2-carboxamido)benzenate], and four novel azido-bridged Mn(II) dimeric complexes, [Mn2(phen)4(mu(1,1)-N3)2][M(III)(bpb)(CN)2]2 x H2O [M = Fe (3), Cr (4), Co (5)] and [Mn2(phen)4(mu(1,3)-N3)(N3)2]BPh4 x 0.5H2O (6), have been synthesized and characterized by single-crystal X-ray diffraction analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 86 publications
(22 citation statements)
references
References 132 publications
2
20
0
Order By: Relevance
“…The least‐squares fits give magnetic parameters of g = 2.03, J = –6.63 cm –1 , and z J′ = –0.12 cm –1 for 1 ; g = 2.03, J = –7.37 cm –1 , and zJ′ = –0.20 cm –1 for 2 ; g = 1.99, J = –4.46 cm –1 , and zJ′ = –0.08 cm –1 for 3 ; and g = 2.01, J = –8.01 cm –1 , and zJ′ = –0.15 cm –1 for 4 . The J values obtained for 1 – 4 are similar to those for the cyanido‐linked Fe III –Mn II complexes13b,14b,21 and octacyanidotungstate‐based W V –Mn II clusters 22. The negative J values undoubtedly suggest that antiferromagnetic interactions are truly operative through the cyanido bridges.…”
Section: Resultssupporting
confidence: 63%
“…The least‐squares fits give magnetic parameters of g = 2.03, J = –6.63 cm –1 , and z J′ = –0.12 cm –1 for 1 ; g = 2.03, J = –7.37 cm –1 , and zJ′ = –0.20 cm –1 for 2 ; g = 1.99, J = –4.46 cm –1 , and zJ′ = –0.08 cm –1 for 3 ; and g = 2.01, J = –8.01 cm –1 , and zJ′ = –0.15 cm –1 for 4 . The J values obtained for 1 – 4 are similar to those for the cyanido‐linked Fe III –Mn II complexes13b,14b,21 and octacyanidotungstate‐based W V –Mn II clusters 22. The negative J values undoubtedly suggest that antiferromagnetic interactions are truly operative through the cyanido bridges.…”
Section: Resultssupporting
confidence: 63%
“…In the 3D framework of 2, the nearest Cu…Cu distance is 5.533 Å. [39] . Different from 1, the temperature dependence of the χ m T product in a 1 kOe field for 2 suggests a weak ferromagnetic coupling between the Cu Ⅱ centers bridged by the diamagnetic NC-W-CN groups ( Figure 8).…”
Section: Crystal Structures Of Complexes 1 Andmentioning
confidence: 99%
“…Recently, Aromí et al found that there is a linear relationship between the exchange coupling constant ( J ) and the Mn–N–Mn bridging angle ( θ ) on the basis of results obtained for only four complexes 15a. We then prepared a series of end‐on azido‐bridged Mn II complexes with the [Mn 2 (phen) 4 (N 3 ) 2 ] 2+ core and improved the J – θ relationship 15b. Apparently, more effort should be exerted to make the assumption of the relation of J and θ more clear.…”
Section: Introductionmentioning
confidence: 98%